MENINGKATKAN KEMAMPUAN BERPIKIR HOTS SISWA DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA PELAJARAN IPAS KELAS 5 SDN 56/I DESA ARO - Mawaddah; Aisyah, Siti; Br Situmorang, Mulyani; Destrinelli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The results of this research include initial data or initial conditions that the researcher obtained from the results of daily tests of class V students at SDN 56/I Aro Village for the 2024/2025 academic year, then improvements were made using Classroom Action Research (PTK) in two cycles of which there were four The stages in each cycle are planning, implementation, observation and reflection. Based on the pre-cycle scores, it is known that of the 19 students there were only 4 students who met the score > KKM (70) while 15 of them had the score < KKM (70). Based on the scores in cycle 1 of the My Regional Culture material, it is known that of the 19 students there were only 9 students who met the score > KKM (70) while 10 of them had the score < KKM (70). Based on the scores in cycle 2 of the Economic Conditions in My Region material, it is known that of the 19 students, only 16 students met the score > KKM (70) while 3 of them had the score < KKM (70). The completeness of individual learning outcomes in the pre-cycle was 4 people with classical completeness reaching 21.05% and the class average score was 62.42, in the first cycle there were 9 students with classical completion reaching 47.37% and the class average score 67.95. Furthermore, the completeness of HOTS thinking skills in cycle II increased, namely by 16 students with classical completeness reaching 84.21% and the average class score obtained was 83.47. Based on the table of student observation results, the Analyze score was 54%, Evaluate was 76%, Create was 100%.   Keywords: HOTS, problem based learning model, thinking ability